Composite cloth for soft roof of open tent automobile and preparation method of composite cloth

By using thermoplastic elastomer composite fabric structure in convertible car soft top materials, combined with waterproof, UV treatment and flame retardant synergist, the problems of insufficient flame retardant, mildew and formaldehyde removal performance of existing materials are solved, and resistance to the present materials is achieved Bending and aging-resistant high-performance material.

CN119239089AActive Publication Date: 2025-01-03JIANGYIN WEITAO PLASTIC NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411313561.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing convertible car soft top materials have poor flame retardant effects, mildew resistance and formaldehyde removal performance, and have a short service life and are prone to mold, which cannot meet consumers' demand for material performance.

Method used

Adopt a composite fabric structure from the outside to the inside, including the exterior finish, the adhesive layer, the intermediate layer and the interior finish. The intermediate layer is a thermoplastic elastomer, containing thermoplastic resin, elastomer, foaming agent, flame retardant masterbatch, and antibacterial Powder and coupling agent, flame retardant masterbatch is a compound of phosphorus-nitrogen composite halogen-free flame retardant and Jinshilanthanum rare earth flame retardant synergistic agent. The exterior and interior finishes are waterproof silicon and UV four-stage treatment. Preparation by kneading, granulating, calendering and high-temperature baking processes.

Benefits of technology

It realizes bending resistance, aging resistance, excellent flame retardant, mildew and formaldehyde removal performance of convertible car soft roof materials, and improves service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119239089A_ABST
    Figure CN119239089A_ABST
Patent Text Reader

Abstract

The invention relates to composite cloth for a soft roof of an open tent automobile and a preparation method of the composite cloth, and is characterized in that the composite cloth comprises an outer decorative surface, a bonding layer, a middle layer, a bonding layer and an inner decorative surface in sequence from outside to inside, the middle layer is a thermoplastic elastomer, and the thermoplastic elastomer is prepared from the following raw materials in parts by mass: 40-60 parts of thermoplastic resin, 1-5 parts of a curing agent, 1-5 parts of a curing agent and 1-5 parts of a curing agent. The invention relates to a flame-retardant plastic, which comprises the following components in parts by weight: 25-50 parts of elastomer, 0.5-2 parts of foaming agent, 8-25 parts of flame-retardant master batch, 1-5 parts of antibacterial powder, 1-3 parts of coupling agent and 0.5-1 part of cross-linking agent. Wherein the antibacterial powder is a compound of far infrared ceramic powder and silver ion antibacterial powder; the flame-retardant master batch is a compound of a phosphorus-nitrogen composite halogen-free flame retardant, a Jinshi lanthanum rare earth flame-retardant synergist and microcapsule-coated red phosphorus. The composite cloth for the soft roof of the open tent automobile is resistant to bending and aging and has excellent flame retardance, mildew resistance and formaldehyde removal performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of multi-layer hot-melt composite materials, and in particular relates to a composite cloth for a convertible car soft top and a preparation method thereof. Background Art

[0002] Convertibles can be divided into hard-top cars and soft-top cars according to the structure of the roof. Among them, soft-top cars are more common, usually using canvas, vinyl or PVC leather as the roof material, equipped with a foldable bracket, which can realize the folding, opening and folding of the roof.

[0003] However, the convertible car soft top roof made of the above simple materials has poor flame retardant effect, poor aging resistance, insufficient softness, and a short service life. In addition, when folded and stored after raining and getting wet, the ordinary cloth surface is prone to mold and produces visible mold spots, which cannot meet consumers' requirements for the various performance of convertible car soft top materials.

[0004] During the car assembly or subsequent decoration process, colloid adhesives containing a large amount of formaldehyde will also be used in the soft top of convertible cars. Formaldehyde has a relatively strong irritating effect on human skin and mucous membranes. Long-term inhalation of formaldehyde can lead to the occurrence of cancers such as leukemia.

[0005] Chinese patent CN202210262874.9 discloses a convertible soft top composite material and a preparation method thereof, wherein the convertible soft top composite material comprises an outer facing, an intermediate layer, and an inner facing; the outer facing is one of a woven fabric, an imitation leather material, and a genuine leather material; the raw material component of the intermediate layer is butyl rubber or halogenated butyl rubber; the inner facing is one of a woven fabric, an imitation leather material, and a genuine leather material; the convertible soft top composite material has excellent waterproof and weather resistance, bonding performance, air tightness, sound insulation effect, light aging resistance, and chemical resistance, but its softness, mildew resistance, and flame retardancy are poor. Summary of the invention

[0006] The purpose of the present invention is to provide a composite fabric for a convertible car soft top and a preparation method thereof. The composite fabric is resistant to bending and aging and has excellent flame retardancy, mildew resistance and formaldehyde removal properties.

[0007] The technical solution adopted by the present invention to solve the above problem is: a composite cloth for a convertible car soft top, the composite cloth comprises, from the outside to the inside, an outer facing, a bonding layer, an intermediate layer, a bonding layer, and an inner facing, the intermediate layer is a thermoplastic elastomer, and the thermoplastic elastomer raw material comprises the following components in parts by weight: 40-60 parts of thermoplastic resin, Elastomer 25-50 parts Foaming agent 0.5-2 parts Flame retardant masterbatch 8-25 parts 1-5 portions of antibacterial powder Coupling agent 1-3 parts Crosslinking agent 0.5-1 part The flame retardant masterbatch is a compound of a phosphorus-nitrogen composite halogen-free flame retardant, a Jinshilan rare earth flame retardant synergist and microcapsule-coated red phosphorus.

[0008] Preferably, the outer surface is one of woven fabric, imitation leather material, and genuine leather material; the inner surface is one of woven fabric, imitation leather material, and genuine leather material; the outer surface and the inner surface are both treated with waterproof silicon and UV level 4 treatment.

[0009] Preferably, the thermoplastic resin is a polyolefin thermoplastic elastomer TPO, and the PP resin in the raw material is selected from ternary copolymer PP, which and EPDM act as base resins, and are a blend with PP as a hard segment and EPDM as a soft segment.

[0010] Preferably, the elastomer is composed of ethylene propylene diene monomer rubber EPDM and styrene-butadiene-styrene block copolymer SEBS; the elastomer SBS has excellent room temperature impact strength and low temperature impact strength for PP, and SEBS, as a hydrogenated product of SBS, makes the temperature resistance and aging resistance more excellent, and when EPDM and SEBS are used together to toughen PP, there is an obvious synergistic effect, and the toughening effect is significantly better than that of single EPDM or SEBS.

[0011] Preferably, the foaming agent is a core-shell structured foaming agent, wherein the outer shell is a thermoplastic acrylic polymer and the inner core is spherical plastic particles composed of alkane gas, which can effectively reduce the weight of the product, produce a uniform and stable closed microporous structure, and play a role in heat insulation.

[0012] Preferably, the antibacterial powder is a compound of far-infrared ceramic powder and silver ion antibacterial powder. Among them, far-infrared ceramic powder can radiate more far-infrared rays than normal objects, has catalytic oxidation function, generates negative monovalent hydroxide ions under sunlight (especially ultraviolet rays), can effectively remove benzene, formaldehyde, sulfide, ammonia and odorous substances in the room, and has a bactericidal function; after the metal ions in the silver ion antibacterial powder contact and react with bacteria, the inherent components of the microorganisms are destroyed or functional disorders are generated. When the bacteria lose their activity, the metal ions will be freed from the bacteria and repeat the bactericidal activity, so its antibacterial effect is long-lasting. In addition, under the action of light, metal ions can play the role of catalytic active centers, activate oxygen in water and air, generate hydroxyl free radicals and active oxygen ions, and active oxygen ions have strong oxidizing ability, which can destroy the reproductive ability of bacteria in a short time and cause cell death, thereby achieving the purpose of antibacterial.

[0013] Preferably, the coupling agent is a powder coupling agent, which has active and polar groups, and integrates various processing aid properties such as dispersion, coupling, internal and external lubrication, etc. Compared with general liquid coupling agents, it has good performance durability and does not precipitate.

[0014] Preferably, the flame retardant masterbatch is prepared by the following preparation method: a phosphorus-nitrogen composite halogen-free flame retardant, a Jinshilan rare earth flame retardant and microcapsule-coated red phosphorus (microencapsulated red phosphorus) in a mass ratio of 7:1:2 are fully mixed in a high-speed mixer at room temperature.

[0015] Preferably, the composite fabric for the convertible car soft top has a thickness of 0.8-2 mm.

[0016] A method for preparing a composite fabric for a convertible car soft top comprises the following steps: Step 1: Put the thermoplastic elastomer raw materials into a kneader according to the ratio for kneading, during which the kneader is kept at a constant temperature. After the raw materials are evenly dispersed, they are conveyed to a twin-screw granulator by a single screw for granulation, and the thermoplastic elastomer particles are obtained after drying; Step 2: The thermoplastic elastomer particles obtained in step 1 are made into a thermoplastic elastomer sheet by a calendering compounding machine under high temperature conditions, and both sides of the thermoplastic elastomer sheet are hot-melt bonded to the outer surface and the inner surface through the bonding layer formed by the hot melt adhesive film of the high temperature resistant release film to obtain a composite cloth; Step three, baking the composite cloth obtained in step two at high temperature to heat-seal and reinforce the composite cloth, and then cooling and shaping the composite cloth to obtain a finished product.

[0017] Preferably, in step 1, the kneading temperature is 130-140°C, the kneading time is 10-20 min, and the temperature of the twin-screw granulator is 150-160°C; in step 2, the high temperature is 130-150°C, and the thickness of the thermoplastic elastomer sheet is 0.3mm-0.8mm; in step 3, the high temperature baking temperature is 180-200°C, and the baking time is 1-2min.

[0018] During the kneading process, the temperature of the kneader should be kept constant at 130-140°C. If the temperature is too high, the thermoplastic resin, elastomer and cross-linking agent will cross-link prematurely, and the dispersion effect in the next process will deteriorate in the twin-screw granulator. In addition, if the temperature is too high, reaching 180-200°C, the foaming agent will also react and foam, making it impossible to smoothly calender the sheet.

[0019] When calendered into sheets, the surface of the produced thermoplastic elastomer has a certain degree of stickiness, and is soft and elastic. It is clamped with a hot-melt adhesive film lined with a high-temperature resistant release film to maintain the size of the sheet without direct contact with the machine's rollers. While peeling off the two layers of high-temperature resistant release film, they are hot-melt bonded to the exterior and interior surfaces that have been treated with waterproof silicone and UV level 4, and then passed through an oven at 180-200 degrees Celsius to control the production speed and ensure that the composite cloth is in the oven for 1-2 minutes. If the time is too short, the foaming will be incomplete, and if the time is too long, the foaming will be over-foamed, which will lead to foam rupture.

[0020] Compared with the prior art, the advantages of the present invention are: The composite fabric for the convertible car soft top is resistant to bending and aging and has excellent flame retardancy, mildew resistance and formaldehyde removal performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a process flow chart of the composite cloth for the convertible car soft top.

[0022] Among them: 1 and 2 are both hot melt adhesive films of high temperature resistant release films, 3 is the winding route for peeling off the high temperature resistant release film, 4 is the unwinding route for the outer surface, 5 is the winding route for peeling off the high temperature resistant release film, and 6 is the unwinding route for the inner surface.

[0023] Figure 2 The diagram is a schematic structural diagram of the composite fabric for the convertible car soft top of the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below with reference to the accompanying drawings.

[0025] A method for preparing a composite fabric for a convertible car soft top comprises the following steps: Step 1, putting the thermoplastic elastomer raw materials into a kneading machine according to the ratio for kneading, during which the kneading machine is kept at a constant temperature of 135°C, kneading for 15 minutes, and then the raw materials are evenly dispersed and conveyed to a twin-screw granulator by a single screw for granulation, and then drying to obtain thermoplastic elastomer particles, wherein the temperature of the twin-screw granulator is 150°C; Step 2: The thermoplastic elastomer particles obtained in step 1 are made into a thermoplastic elastomer sheet at a temperature of 140° C. using a calendering compounding machine, wherein the thickness of the thermoplastic elastomer sheet is 0.5 mm, and both sides of the thermoplastic elastomer sheet are respectively clamped with hot melt adhesive films with high temperature resistant release films, and while peeling off the two layers of high temperature resistant release films, the outer surface (woven fabric treated with waterproofing) and the inner surface (woven fabric treated with waterproofing) are respectively hot melt bonded to the two sides of the thermoplastic elastomer sheet to obtain a composite cloth; Step 3: bake the composite cloth obtained in step 2 at 200°C for 2 minutes to heat-seal and reinforce the composite cloth, and then cool and shape it to obtain a finished product.

[0026] The mass proportions of the raw materials in Examples 1-5 are shown in Table 1.

[0027] Among them, the thermoplastic resin is British INEOS KV329; the elastomer is a compound of SEBS YH-688 (Yueyang Petrochemical) and EPDM311PM (Sinopec), with a mass ratio of 1:1; the foaming agent is Guangdong Benqi NS-1530C; the antibacterial powder is silver ion antibacterial powder KF136 (Huizhou Mingkai) and 1250 mesh far-infrared ceramic powder (Tianjin Hongyan), with a mass ratio of 3:2; the coupling agent is Guangzhou Yuantai YY5021; the cross-linking agent is Jiangsu Huaxing TAIC.

[0028] The flame retardant masterbatch is prepared by the following preparation method: (1) Preparation of phosphorus-nitrogen composite halogen-free flame retardant: The phosphorus-based flame retardant (phosphate ester) and the nitrogen-based flame retardant (melamine) are stirred and mixed in a mass ratio of 1:1. Water is added during the mixing process to ensure uniform mixing. After mixing, the powdered phosphorus-nitrogen composite halogen-free flame retardant is obtained by spray drying.

[0029] (2) The nitrogen-phosphorus compound flame retardant, the Jinshilan rare earth flame retardant synergist, and the microcapsule-coated red phosphorus in a mass ratio of 7:1:2 are fully mixed in a high-speed mixer at room temperature.

[0030] Table 1:

[0031] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that the thermoplastic resin uses injection molding grade Sinopec Maoming HT9025M.

[0032] Comparative Example 2: The only difference between Comparative Example 2 and Example 1 is that the flame retardant masterbatch uses the polypropylene halogen-free flame retardant masterbatch HB115 produced by Huabiao Plastics.

[0033] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the antibacterial powder uses KF136 alone, that is, all silver ion antibacterial agents are used.

[0034] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the antibacterial powder uses 1250 mesh far-infrared ceramic powder alone, that is, all far-infrared ceramic powder is used.

[0035] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that the temperature of the kneading machine is 160 degrees.

[0036] Comparative Example 6: The only difference between Comparative Example 6 and Example 1 is that after being calendered into a sheet, only a high-temperature release film is used for backing, and no hot-melt adhesive film is used.

[0037] The composite fabrics of Examples 1-5 and Comparative Examples 1-6 were subjected to performance tests, wherein the performance test results of Examples 1-5 are shown in Table 2, and the performance test results of Comparative Examples 1-6 are shown in Table 3.

[0038] Table 2 Performance test results of Examples 1-5

[0039] Table 2 Performance test results of comparative examples 1-5

[0040] As can be seen from the above table, compared with Example 1, the injection molding grade PP HT9025M used in Comparative Example 1 has poor dispersibility effect at 135 degrees of kneading machine process; Comparative Example 2 uses Huabiao Plastic's polypropylene halogen-free flame retardant masterbatch-HB115, and the flame retardant effect is general; Comparative Example 3 uses Huizhou Mingkai KF136, and Comparative Example 4 uses Tianjin Hongyan 1250 mesh far-infrared ceramic powder. It can be seen that the silver ion antibacterial powder and the far-infrared ceramic powder have a synergistic effect, especially for the removal of formaldehyde; Comparative Example 5 The temperature of the kneader and the twin screw are too high, resulting in uneven dispersion and uneven foaming of the thermoplastic elastomer, resulting in large fluctuations in product testing; Comparative Example 6 has no hot melt adhesive film, the base cloth and the thermoplastic elastomer sheet are not adhered, the finished product trial production failed, and the experimental data is marked with NG.

[0041] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.

Claims

1. A composite fabric for a convertible car soft top, characterized in that: The composite cloth comprises, from outside to inside, an outer facing, a bonding layer, an intermediate layer, a bonding layer, and an inner facing, wherein the intermediate layer is a thermoplastic elastomer, and the thermoplastic elastomer raw material comprises the following components in parts by weight: 40-60 parts of thermoplastic resin, Elastomer 25-50 parts Foaming agent 0.5-2 parts Flame retardant masterbatch 8-25 parts 1-5 portions of antibacterial powder Coupling agent 1-3 parts Crosslinking agent 0.5-1 part The antibacterial powder is a compound of far-infrared ceramic powder and silver ion antibacterial powder; the flame retardant masterbatch is a compound of phosphorus-nitrogen composite halogen-free flame retardant, Jinshilan rare earth flame retardant synergist and microcapsule-coated red phosphorus.

2. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The outer surface is one of woven fabric, imitation leather material, and genuine leather material; the inner surface is one of woven fabric, imitation leather material, and genuine leather material; the outer surface and the inner surface are both treated with waterproof silicon and UV level 4 treatment.

3. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The thermoplastic resin is polyolefin thermoplastic elastomer TPO.

4. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The elastomer is composed of ethylene propylene diene monomer rubber EPDM and styrene-butadiene-styrene block copolymer SEBS.

5. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The foaming agent is a foaming agent of a core-shell structure, wherein the shell is a thermoplastic acrylic polymer and the core is spherical plastic particles composed of alkane gas.

6. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The coupling agent is a powder silane coupling agent.

7. The composite fabric for convertible soft top according to claim 1, characterized in that: The mass ratio of the phosphorus-nitrogen composite halogen-free flame retardant, the Jinshilan rare earth flame retardant synergist and the microcapsule-coated red phosphorus is 7:1:

2.

8. The composite fabric for a convertible car soft top according to claim 1, characterized in that: The thickness of the composite fabric for the convertible car soft top is 0.8-2 mm.

9. A method for preparing a composite fabric for a convertible car soft top according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Put the thermoplastic elastomer raw materials into a kneader according to the ratio for kneading, during which the kneader is kept at a constant temperature. After the raw materials are evenly dispersed, they are conveyed to a twin-screw granulator by a single screw for granulation, and the thermoplastic elastomer particles are obtained after drying; Step 2: The thermoplastic elastomer particles obtained in step 1 are made into a thermoplastic elastomer sheet under high temperature conditions by a calendering compounding machine, and hot melt adhesive films with high temperature resistant release films are respectively attached to both sides of the thermoplastic elastomer sheet, and then the high temperature resistant release films are peeled off respectively, and the formed adhesive layers are successively hot-melt bonded to the outer surface and the inner surface to obtain a composite cloth; Step three, baking the composite cloth obtained in step two at high temperature to heat-seal and reinforce the composite cloth, and then cooling and shaping the composite cloth to obtain a finished product.

10. The method for preparing a composite fabric for a convertible car soft top according to claim 9, characterized in that: In step 1, the kneading temperature is 130-140°C, the kneading time is 10-20 min, and the temperature of the twin-screw granulator is 150-160°C; in step 2, the high temperature is 130-150°C, and the thickness of the thermoplastic elastomer sheet is 0.3mm-0.8mm; in step 3, the high temperature baking temperature is 180-200°C, and the baking time is 1-2min.

Citation Information

Patent Citations

  • Composite material for soft top of convertible and preparation method of composite material

    CN114654839A

  • Rear earth organic phosphonate flame retardant, synthesizing method and use thereof

    CN101475706A

  • Halogen-free inflaming retarding thermoplastic elastomer for secondary injection adhering and preparation method thereof

    CN102140224A

  • Ultrahigh-fluidity thermoplastic elastomer for automobile parts and preparation method thereof

    CN116120672A

  • Far infrared negative ion antibacterial anti-mite health-care multifunctional fiber and preparation and application thereof

    CN116288768A